1993
DOI: 10.1111/j.1365-3040.1993.tb00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Root demography in kiwifruit (Actinidia deliciosa)

Abstract: A rhizotron was used to study fine‐root demography in mature vines of kiwifruit (Actinidia deliciosa). The vines were grown in a deep, well drained, silt loam and received normal orchard management. Roots were measured from 10 to 160cm depth at biweekly intervals for 2 years. After an initial phase of rapid colonisation of the repacked soil behind the rhizotron windows, the total length of visible roots per vine remained quite steady. This apparent stability of the total belied fast and sustained localized tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…This result is in agreement with that of Reid, Sorenson, and Petrie (1993) whose study showed longer life spans for higher-order roots of kiwifruit (Actinidia deliciosa). This result is in agreement with that of Reid, Sorenson, and Petrie (1993) whose study showed longer life spans for higher-order roots of kiwifruit (Actinidia deliciosa).…”
Section: Root Morphology and The Risk Of Mortality-supporting
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with that of Reid, Sorenson, and Petrie (1993) whose study showed longer life spans for higher-order roots of kiwifruit (Actinidia deliciosa). This result is in agreement with that of Reid, Sorenson, and Petrie (1993) whose study showed longer life spans for higher-order roots of kiwifruit (Actinidia deliciosa).…”
Section: Root Morphology and The Risk Of Mortality-supporting
confidence: 93%
“…Higher mortality among younger roots (or early in the life of a root cohort) has been reported in an Alaskan taiga forest (Ruess, Hendrick, and Bryant, 1998) and a New Zealand kiwi orchard (Reid, Sorenson, and Petrie, 1993). Higher mortality among younger roots (or early in the life of a root cohort) has been reported in an Alaskan taiga forest (Ruess, Hendrick, and Bryant, 1998) and a New Zealand kiwi orchard (Reid, Sorenson, and Petrie, 1993).…”
mentioning
confidence: 97%
“…To accurately estimate biomass turnover contributed by each order, we must know the turnover rate, as well as the biomass of each order (Richardson and zu Dohua 2003). In contrast with the higher orders, the first order roots are the most dynamic part of the root system (Wells and Eissenstat 2001;Hishi and Takeda 2005a, b), and can turnover twice as fast as the second order roots (Reid et al 1993;Wells 1999;Majdi et al 2001;Wells et al 2002). If first order roots have a total biomass that is equal or greater than the second order roots, as found for the two species studied here and the seven out of nine species in Pregitzer et al (2002), the proportion of total fine root biomass turnover (which is calculated as the multiplication of turnover rate and standing biomass) being accounted for by the first order would be at least twice of that by the second order.…”
Section: Biomass Allocation Patterns Across Different Branch Ordersmentioning
confidence: 99%
“…Data sources includeAnderson et al (2003),Baddeley and Watson (2005),Coleman et al (2000),Gill et al (2002),Kern et al (2004),King et al (2002),Krasowski et al (2010),Ponti et al (2004),Stover et al (2010),Tierney and Fahey (2001),Wells and Eissenstat (2001),Wells et al (2002), andYao et al (2006) and (B) root branching order (y = 1.913 + 0.189x, R 2 = 0.181, P < 0.001). Data sources includeEspeleta et al (2009), Gang et al (2012,Guo et al (2008),Huang et al (2010),Majdi et al (2001),Reid et al (1993),Valenzuela-Estrada et al (2008),Wells et al (2002), andXia et al (2010).…”
mentioning
confidence: 99%